Evaluating the Role of Breast Ultrasound and Mammography in Early Detection of Breast Cancer at the National Cancer Institute in Misurata, Libya - Mohamed Ben Taher; Mona Gerriow; Shaima Bensasi; Esra Obeid; Eman Ghabag; Mohamed Almajdub (AlQalam Journal of Medical and Applied Sciences, 2025)
Breast cancer is one of the biggest health dilemmas worldwide and remains a leading cause of death among women, particularly when diagnosed at advanced stages. Consequently, early and accurate detection is a cornerstone in improving survival rates and ensuring the effectiveness of therapeutic interventions. Mammography is globally recognized as the primary screening tool for the early detection of breast cancer due to its ability to identify subtle tissue changes. However, its diagnostic accuracy is significantly compromised in women with dense breast tissue, which reduces sensitivity and increases the likelihood of missed lesions. In such contexts, ultrasound emerges as an essential complementary modality that enhances the overall diagnostic performance. This study aimed to compare the diagnostic accuracy of ultrasound and mammography in detecting abnormal breast masses in Misurata, Libya. A retrospective cross-sectional study of 100 women with an average age of 50 years (range: 15–95) who underwent both ultrasound and mammography in 2024. Mammography served as a provisional reference standard because histopathological confirmation was not available for all cases. ROC curves and Chi-square, Cochran, and Mantel-Haenszel tests with the significance level set at 0.05 (a=0.05) were used to assess diagnostic performance. Ultrasound showed excellent diagnostic accuracy with AUC = 0.916 (Right breast) and 0.960 (Left breast). Sensitivity was 90.9% (Right breast) and 100% (Left breast), while specificity was 92.3% and 92%, respectively. No significant differences were found between ultrasound and mammography (p > 0.05). Ultrasound demonstrates high diagnostic accuracy comparable to mammography, particularly in dense breasts. In resource-limited settings, the combined use of ultrasound and mammography is recommended to optimize detection.